Challenges for Nurses in Disaster Management: A Scoping Review - Al Harthi M; Al Thobaity A; Al Ahmari W; Almalki M (Dove Medical Press, 2020)
Manal Al Harthi,1,2 Abdulellah Al Thobaity,1 Waleed Al Ahmari,1 Mohammed Almalki1 1Nursing Department, College of Applied Medical Sciences, Taif University, Ta’if, Saudi Arabia; 2King Faisal Medical Complex, Ministry of Health, Taif, Saudi ArabiaCorrespondence: Abdulellah Al ThobaityTaif University, P. O. Box 11099, Taif 21944, Saudi ArabiaTel +966 12-727-2020Email a.thobaity@tu.edu.saAbstract: To reduce the impact of disasters, healthcare providers, especially nurses, need to be prepared to respond immediately. However, nurses face several challenges in all phases of disaster management. The findings of a literature review based on scoping approaches, which utilized the Joanna Briggs Institute methodology, indicated that the major barriers facing nurses include the following: (1) disaster nursing is a new specialty; (2) inadequate level of preparedness; (3) poor formal education; (4) lack of research; (5) ethical and legal issues; and (6) issues related to nurses’ roles in disasters. Educators, researchers, and stakeholders need to make efforts to tackle these issues and improve disaster nursing.Keywords: disaster nursing, disaster preparedness, disaster response, challenges